Potensi Pola Perjalanan Wisata Gastronomi di Kota Cirebon - Rakhmat Alief Marthaputra; Dewi Tugarini; Woro Priatini (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2021)
Cirebon has a diverse tourism potential, including historical tourism, pilgrimage tourism, cultural tourism, and gastronomic tourism. The existence of three sultanates, as well as the pilgrimage destination of Sunan Gunung Jati, contributed to the wealth of tourism. The city also has a plethora of gastronomic tourism, which is heavily influenced by the historical tourism of the three sultanates. Currently, the city is not supported by gastronomic travel patterns that its stakeholders have socialized. The author employed a qualitative research method with a descriptive approach. Data for this study were gathered through observation and interviews.